Factors Associated with High Fat, Salt, And Sugar Food Selection on Online Food Delivery Service Among Students of SMAN (State High School) 47 Jakarta in 2022 - Arifiana Arifiana; Kusharisupeni Djokosujono; Wahyu Kurnia Yusrin Putra; Nina Muziana (Faculty of Public Health Universitas Indonesia, 2022)
In the use of Online Food Delivery Service (OFDS), an online service applying a smartphone to make it easier for users to get food quickly, it was found that the foods selected tend to be unhealthy and may increase the risk of being overweight. The aim of this study was to determine predominant and other factors that differ in food selection in OFDS among students at SMAN (State High School) 47 Jakarta in 2022. This study applied a cross-sectional study design with 112 subjects. Data were taken through a questionnaire and analyzed by using an X²- test and multiple logistic regression. This study shows that 58.9% of students chose foods categorized as high in fat, salt, and sugar (HFSS) with fried chicken as the food type chosen the most. Bivariate results show that gender, reward sensitivity, OFDS frequency, and reduction in price, are all significantly different in the selection of foods ordered through OFDS. A multiple logistic regression analysis shows OFDS frequency as a predominant factor (OR=6,89). This study suggests that the school may collaborate with public health centers district health offices or colleges in nutritional sciences on providing nutrition education. This study also suggests that the government must apply high taxes on HFSS foods.